Association Between LDL-to-HDL Cholesterol Ratio and Albuminuria in Patients With Type 2 Diabetes Mellitus: A Cross- Sectional Study - Jeremia Siregar; Michelle Audrey Widuri Hutapea; Angeline Tancherla; Andree Kurniawan; Stephanie Marisca (Fakultas Kedokteran Universitas Pelita Harapan, 2026)
Background: Dyslipidemia plays a role in the pathogenesis of diabetic kidney disease, yet the clinical utility of the LDL/HDL ratio for detecting early renal involvement remains uncertain. This study evaluated the association between LDL/HDL ratio and albuminuria in type 2 diabetes mellitus (T2DM) patients. Methods: A cross-sectional study was conducted using medical records of adults with T2DM at Siloam Hospital Lippo Village, Indonesia. Patients with complete lipid profiles and urine albumin–creatinine ratio (ACR) data were included. The LDL/HDL ratio was analyzed in relation to albuminuria. Receiver operating characteristic (ROC) analysis determined the optimal cutoff. The ratio was dichotomized using this cutoff, and associations with albuminuria were evaluated using chi-square tests and Poisson regression with robust variance to estimate adjusted prevalence ratios (aPRs). Result: A total of 95 patients were analyzed, of whom 46.3% had albuminuria. The LDL/HDL ratio correlated with ACR (ρ=0.528, p<0.001). ROC analysis showed good discrimination for albuminuria (AUC 0.796; 95%CI 0.704–0.888), with a bootstrap 95%CI 0.700–0.881. The optimal cutoff was 2.435, yielding 77.3% sensitivity and 74.5% specificity. Albuminuria was more frequent in patients with LDL/HDL ≥2.435 than in those below the cutoff (72.3% vs. 20.8%; p<0.001). LDL/HDL ≥2.435 was independently associated with albuminuria (aPR 3.03; 95%CI 1.82–5.26; p<0.001). Hypertension, older age, and higher HbA1c were also significant predictors. Conclusion: The LDL/HDL ratio showed acceptable discriminatory performance and was independently associated with albuminuria in patients with T2DM. This simple index may serve as an adjunctive marker for renal risk stratification, pending external validation in larger prospective studies.